IMPROVE THE PERFORMANCE OF LINEAR ARRAY BY REDUCING SIDE LOBE LEVEL AND BEAM STEERING BY GENETIC ALGORITHM (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
This paper describes advanced methods for adaptive beam forming for linear antenna array to reduce the side lobe level (SLL) towards the main beam. for reduction of side lobe level and beam steering, we are introducing the genetic algorithm .genetic algorithm is a optimization method which work on the principle of survival of fittest and implemented using computer simulation .genetic algorithm can determine the various values of phase excitation for each antenna element to steer the main beam in specific location .this technique provide its effectiveness in improving the performance of the antenna array. This application is used in smart antenna for wireless communication, mobile communication.